From cotenyou to continue: modeling the contributions of phonological and morphological awareness to spelling accuracy in young Spanish-English dual-language learners - Durant, Kathleen; Oddo, Mary; Harrell-Williams, Leigh; Jarmulowicz, Linda (Frontiers in Education, 2025)
PurposeThis study evaluates a developmental model of predictive relationships between oral-language based metalinguistic skills in kindergarten and single-word reading and spelling in second grade for Dual-language Learning (DLL) children.MethodsSeventy-one Spanish-speaking English-learning children participated in this longitudinal study. A partial-least squares path model investigated how cross-linguistic Phonological Awareness in kindergarten predicted English Morphological Awareness (MA) and later English literacy performance (single-word reading and spelling) in second grade.ResultsSpanish Phonological Awareness (S-PA) at the end of kindergarten predicted 2nd grade English MA (E-MA) development and indirectly facilitated spelling performance. English Phonological Awareness (E-PA) at the end of kindergarten uniquely supported 2nd grade word reading and spelling accuracy. Within the model, S-PA was the only significant longitudinal predictor of E-MA, and E-PA was the predictor most strongly associated with spelling skill, overall.ConclusionChildren learning more than one language are able to leverage first language knowledge dynamically to support second language literacy outcomes over time. Study results suggest DLL children's phonological awareness in both languages should be assessed in kindergarten to more accurately estimate risk-status for poor literacy performance over time.